Fathering in Australia among couple families with young children - Baxter, Jennifer; Smart, D (My University, 2011)
This report aims to increase understanding of the many ways in which fathers in couple families with young children contribute to family life, through the study of their time investment with children, their supportiveness as partners, their financial contribution, their parenting behaviours and styles, and their perceptions of their own adequacy as fathers. The impact of fathers on children's wellbeing is also examined. The report uses data from Waves 1 to 3 of Growing Up in Australia: the Longitudinal Study of Australian Children (LSAC), a large-scale, nationally representative study of children and families.
Occassional Paper Series
Keywords: Families -- Fathers; Families; Families -- Parents and Parenting; Families and relationships; Families; Parents and Parenting; Fathers; Families and relationships